CD8 T cells are dispensable for experimental autoimmune prostatitis induction and chronic pelvic pain development - Salazar, Florencia C.; Martínez, Maria S.; Paira, Daniela A.; Chocobar, Yair A.; Olivera, Carolina; Godoy, Gloria J.; Acosta Rodríguez, Eva V.; Rivero, Virginia E.; Motrich, Ruben D. (2024)
Impact Factor: 5.5